Methodological benchmarking of GATE and TOPAS for 6 MV LINAC beam modeling and simulation efficiency - Elcadi, Zakaria Ait; Toufique, Yassine; Torfeh, Tarraf; Sukumaran, Renilmon; Hammoud, Rabih; Al-Hammadi, Noora; Bouhali, Othmane (Frontiers in Physics, 2025)
Monte Carlo simulations are widely used in medical physics to model particle interactions for accurate radiotherapy dose calculations. This study presents a methodological comparison between two leading Geant4-based simulation platforms-GATE and TOPAS-for modeling a 6 MV Varian CLINAC IX linear accelerator. The objective was to evaluate and optimize the performance of both platforms in terms of computational efficiency and dosimetric accuracy. Simulations were validated against experimental measurements using percentage depth dose and dose profiles acquired in a water phantom. Methods included geometry modeling, electron source parameter tuning, and implementation of phase space files, production thresholds, and variance reduction techniques. Results showed that TOPAS provided superior agreement with experimental data, especially in deep dose regions, while GATE offered marginally better computation times when advanced variance reduction tools were applied. These findings highlight the importance of aligning simulation platform choice with specific clinical or research objectives. This work offers a practical reference for medical physicists and researchers seeking to optimize Monte Carlo simulations for treatment planning, quality assurance, or commissioning of radiotherapy systems.